Evaluasi Program Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Model Cipp - Nopi Aprilia; Misnaniarti Misnaniarti; Novrikasari Novrikasari; Wahyu Dwi Ari Wibowo (Jurnal Keperawatan Silampari, 2023)
This study aims to evaluate the DHF mosquito nest eradication program (PSN) using the CIPP model. The method used is a qualitative research design with analytical descriptive data. The results showed that the DHF program manager knew the context factor; the input factor indicated that human resources were sufficient in PSN activities, but more than the facilities/infrastructure and funds were needed. The process factor told that PSN DBD activities had been carried out but needed to be more optimal because of community barriers. Who must know the importance of PSN and inactive larva monitoring cadres (JUMANTIK)? At the same time, the product factor for PSN activities is still low because it is only carried out during high cases and the rainy season. In conclusion, PSN activities must be carried out routinely to reduce the breeding of DHF mosquitoes by involving the community through the one house one Friday movement (GIRIJ). Keywords: DHF, KLB; Lubuklinggau, PSN